2015
DOI: 10.1080/10408398.2013.865590
|View full text |Cite
|
Sign up to set email alerts
|

Ginger—Mechanism of action in chemotherapy-induced nausea and vomiting: A review

Abstract: Despite advances in antiemetic therapy, chemotherapy-induced nausea and vomiting (CINV) still poses a significant burden to patients undergoing chemotherapy. Nausea, in particular, is still highly prevalent in this population. Ginger has been traditionally used as a folk remedy for gastrointestinal complaints and has been suggested as a viable adjuvant treatment for nausea and vomiting in the cancer context. Substantial research has revealed ginger to possess properties that could exert multiple beneficial eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 47 publications
2
100
1
2
Order By: Relevance
“…First, this study has demonstrated that both ginger extracts and the compounds, 6-gingerol and 6-shogaol, noncompetitively inhibited 5-HT 3 receptor activation. This provides both support for ginger interacting with the 5-HT 3 receptors in humans but also provides additional evidence that these compounds bind to a currently unknown binding site, distinct from other types of 5-HT 3 ] noted, this may allow for potentially synergistic inhibition of 5-HT 3 signalling when combined with standard 5-HT 3 antagonists (e.g. ondansetron, a common antiemetic during chemotherapy and surgery).…”
Section: Mechanisms Of Actionmentioning
confidence: 87%
See 1 more Smart Citation
“…First, this study has demonstrated that both ginger extracts and the compounds, 6-gingerol and 6-shogaol, noncompetitively inhibited 5-HT 3 receptor activation. This provides both support for ginger interacting with the 5-HT 3 receptors in humans but also provides additional evidence that these compounds bind to a currently unknown binding site, distinct from other types of 5-HT 3 ] noted, this may allow for potentially synergistic inhibition of 5-HT 3 signalling when combined with standard 5-HT 3 antagonists (e.g. ondansetron, a common antiemetic during chemotherapy and surgery).…”
Section: Mechanisms Of Actionmentioning
confidence: 87%
“…Ginger contains a wide array of bioactive compounds, which have been investigated for their effects on nausea and vomiting. Multiple potential mechanisms of action have been identified including 5-HT 3 receptor antagonism, antiinflammatory properties, and the modulation of gastrointestinal motility [3]. Clinical studies have also reported promising results, and ginger has now been investigated as a treatment for a several types of nausea including motion sickness, postoperative nausea and vomiting, morning sickness, and chemotherapy-induced nausea and vomiting (CINV) [4].…”
Section: Introductionmentioning
confidence: 98%
“…These receptors are expressed in the central nervous system in regions involved in gag reflex and vomiting . Receptor antagonists, such as ondansetron, are used as a standard of care postoperatively and in controlling chemotherapy‐induced nausea and vomiting . Moreover, 5‐HT 3 receptors have been linked to peristaltic activity in the GI tract, as shown by antagonism altering GI motility in vitro .…”
Section: Methodsmentioning
confidence: 99%
“…Ginger, Zingiber officinale roscoe rhizomes ( Zingiberaceae ), is one of the most commonly consumed spices worldwide. Ginger has been used as an herbal medicine to relieve nausea/vomiting and gastrointestinal discomforts (bloating and pain), but the cellular and molecular mechanisms of its neuronal actions are still unclear . It is known that the pharmacological effect of ginger is mainly produced by its bioactive phytochemicals, including the pungent principle gingerols (including 4‐, 6‐, 8, 10‐, and 12‐gingerols) and their more bioactive dehydrated products, the shogaols (including 6‐, 8‐, and 10‐shogaols) …”
Section: Introductionmentioning
confidence: 99%
“…Secondly, as herbal medicine, ginger is known for its anti‐emesis effect. Vagal afferents in the GI tract play an important role in mediating emetic sensation and reflex . Thus, ginger might display its anti‐emesis effect through its interaction with vagal afferents in the GI tract.…”
Section: Introductionmentioning
confidence: 99%